Multi-Stakeholder Collaboration in Implementing Sustainable Logistics: A Case Study of Regional Supply Chains in Southeast Asia - Kasrim; Nur Wahyuni; Risza Presty Rumani (Maneggio, 2025)
This study aims to analyze the dynamics of multi-stakeholder collaboration in implementing sustainable  logistics across Southeast Asia using a Systematic Literature Review (SLR) approach. In the context of regional  economic integration, collaboration among governments, private sectors, academia, and civil society plays a pivotal role in achieving environmentally friendly and resilient supply chain efficiency. The study reviewed 85 scholarly publications from 2015 to 2025 focusing on collaborative governance, digital innovation, and cross-border green logistics practices. The findings reveal that logistics research trends in ASEAN have shifted from cost-efficiency to technology integration and social sustainability. Multi-stakeholder collaboration significantly enhances distribution efficiency, strengthens supply chain resilience, and expands MSME participation in the digital logistics ecosystem. Nevertheless, challenges persist in the form of technological disparities, fragmented regulations, and limited digital literacy in developing economies. Guided by the collaborative governance framework and Triple Bottom Line principles, this research concludes that sustainable logistics requires intersectoral synergy driven not only by technological innovation but also by adaptive, transparent, and value-based governance.